Myanmar's Changing Political Landscape Old and New Struggles - Takeda, Makiko; Yamahata, Chosein (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
Myanmar has faced numerous divisions that hinder its democratization and peacebuilding processes since emerging out of decades of military dictatorship. The coup d'état in 2021 terminated Myanmar's limited and nascent democratization under the civilian leadership of the National League for Democracy (NLD); not only did the coup regime resurface old struggles, but also created new ones. Against the backdrop of Myanmar's changing political landscapes from military to quasi-civilian to civilian rule in 2016, and back to military rule in 2021, the book discusses the various forms of interconnected struggles, both old and new. In this process, the contributed chapters come together to highlight the changing dynamics of stakeholders, relations between agents and beneficiaries, and the generated evolutionary processes in Myanmar's democratization and its reversal. This book brings an even mix of researchers both within and outside of Myanmar to critically discuss how different agents and their interactions, in the form of center-periphery as well as state-non-state relations, continuously shape today's political landscape. Its interdisciplinary composition also invites readers from various backgrounds to grasp with engaged research that identifies the various challenges and addresses ways in which to facilitate change from local and international perspectives.
Part I: Introduction: Challenging Reality -- Chapter 1 Post-Coup Myanmar: Military, Divisions and Atrocities -- Chapter 2 NLD's Governance in Myanmar's Short-lived Democracy: Reforms, Weakness and Challenges -- Chapter 3 Aung San Suu Kyi's Leadership and its Contradictions: General Election of November 2020 -- Part II: Struggling Myanmar -- Chapter 4 Language Policy, Ethnic Identity, and Majority-Minority Relations in Myanmar -- Chapter 5 A Threatened Identity in Chinland of Burma/Myanmar: A Glimpse of Freedom of Religion and Belief -- Chapter 6 Development Policy and Processes in Kachin State: Development from Above during the Ceasefire Period (1994-2010) -- Chapter 7 Ethnic Children at the Thai-Burma Border: Community-Based Organizations Protecting the Rights and Equality -- Chapter 8 The Role of Tatmadaw in Myanmar's Transformation: A Burmese Version of Indonesia's Dwifungsi -- Chapter 9 Failure of Third Force's Role in Unlinking Myanmar's Political Changes with Aung San Suu Kyi -- Part III: Conclusion: A Promising Future? -- Chapter 10 Hope at the End of the Tunnel: Myanmar's Civil Disobedience Movement and Moving Toward a More Inclusive Myanmar -- Chapter 11 Fracturing the Monolith: Could Military Defections End the Dictatorship in Myanmar? -- Chapter 12 For Myanmar from my Adopted Country: Collective Resistance and New Revolution against Military Dictatorship -- Chapter 13 The National Unity Government: Legitimacy and Recognition -- Chapter 14 Japan's "Special Relations" to Serious Warning: A Potential Change in Course? -- Index.
Keywords: Asia -- Politics and government; Economics; Social policy; Social structure; Equality; Comparative government; Ethnology; Culture; Asian Politics; Political Economy and Economic Systems; Social Policy; Social Structure; Comparative Politics; Regional Cultural Studies